Analyzing and modeling the influence of workpiece thickness on geometry of slot machining wire EDMs - Khan, Ahsan Ali; Al Hazza, Muataz Hazza Faizi; Che Daud, Mohd Radzi; Ali , Mohammad Yeakub; Jamingan, Hazira (The Institute of Electrical and Electronics Engineers, Inc., 2016)
Wire erosion discharge machining is one of the non-traditional machining processes which use heat energy of spark to remove material from work piece. Process parameters have given the major influence of the cutting performance on wire EDM. Parameters such as pulse on time, peak current, wire diameter and discharge current are well known for their effect surface roughness and recast layer. The present work aimed to investigate the influence of: thickness, current and wire speed on the machining surface. The surface roughness and hardness have been analyzed assessed. It was conclude that surface roughness increase with the increase of thickness and current, and decrease when wire speed increase. Meanwhile, as work piece thickness increase, the surface hardness increase but it decreases when current and wire speed increases.